Program Posyandu Virtual di Masa Pandemi Mampu Menjaga Tumbuh Kembang Anak: Virtual Posyandu Program during the Pandemic Maintained Children’s Growth and Development - Marchianti, Ancah Caesarina Novi; Rachmawati, Dwita Aryadina; Kusuma, Irawan Fajar; Sudarmanto, Yohanes (Universitas Airlangga, 2024)
Background: Posyandu program suspension due to COVID-19 has resulted in a decrease in monitoring children’s growth, leading to undetected problems. Understanding mothers' eating behavior plays a crucial role in preventing malnutrition, we must continue the program as a health promotion medium to enhance mothers' understanding and track children's growth and development. Objectives: This research aimed to determine the effectiveness of virtual Posyandu program in strengthening cadre health promotion services for nutritionally vulnerable children in Jember Regency agricultural area during the absence of offline Posyandu. Methods: The research was carried out September 2022-January 2023, implementing a 21-day intervention on 169 respondents from Puskesmas Arjasa and Paleran (representing two different socio-cultures). The cadres utilized the application to enhance children's nutritional health and instruct parents on its usage. The success parameter is that there were significant differences between the growth and development of children pre- and post-program. Growth variables were assessed by measuring nutritional status according to Ministry-of-Health Regulation, before and after the intervention, while development variables were assessed using a Developmental Pre-Screening questionnaire (DPSQ). Results: The virtual Posyandu program in both Puskesmas demonstrated significant differences (p<0.001) in children's growth and development parameters, such as height-for-age, weight-for-height, and DPSQ, between the pre- and post-program periods. Despite the challenges posed by the pandemic, the program has effectively maintained children's growth and development. Conclusions: Balitagrow© Android-based application in virtual Posyandu program effectively maintained children’s growth and development in pandemic era and worth continuing to be developed according to user needs.